2019
DOI: 10.3389/fimmu.2019.02801
|View full text |Cite
|
Sign up to set email alerts
|

ILC2s: New Actors in Tumor Immunity

Abstract: Innate lymphoid cells (ILCs) represent the most recently identified family of innate lymphocytes that act as first responders, maintaining tissue homeostasis and protecting epithelial barriers. In the last few years, group 2 ILCs (ILC2s) have emerged as key regulators in several immunological processes such as asthma and allergy. Whilst ILC2s are currently being evaluated as novel targets for immunotherapy in these diseases, their involvement in tumor immunity has only recently begun to be deciphered. Here, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 116 publications
(117 reference statements)
0
31
0
Order By: Relevance
“…Two distinct subsets of ILC2 have been described: resident natural ILC2 and inflammatory ILC2, which can be induced upon IL-33 stimulation (81). High numbers of ILC2 can be found in many IL-33-enriched tumors, although their role in cancer immunity remains controversial (82). Ikutani et al first described an anti-tumoral role of ILC2 in a mouse model of melanoma.…”
Section: Il-33 As An Enhancer Of Anti-tumor Activities Of Ilc2mentioning
confidence: 99%
“…Two distinct subsets of ILC2 have been described: resident natural ILC2 and inflammatory ILC2, which can be induced upon IL-33 stimulation (81). High numbers of ILC2 can be found in many IL-33-enriched tumors, although their role in cancer immunity remains controversial (82). Ikutani et al first described an anti-tumoral role of ILC2 in a mouse model of melanoma.…”
Section: Il-33 As An Enhancer Of Anti-tumor Activities Of Ilc2mentioning
confidence: 99%
“…While tumor-infiltrating NK cells are often associated with a good prognosis, the accumulation of ILC1s that have transdifferentiated from NK cells is correlated with a loss of anti-tumor protection 104 . Although immunosuppressive functions have been attributed to ILC2s found in tumors through their production of type 2 cytokines and enhancement of myeloid-derived suppressor cell function 105 , the role of these cells in tumor immunity is still fairly limited 106 . A recent study demonstrated that ILC2s could induce potent anti-tumor responses in pancreatic cancer and were associated with anti-PD-1 therapy efficacy 107 .…”
Section: Resident Innate Cells Are New Potent Drivers Of Tumor Protecmentioning
confidence: 99%
“…Studies have shown that several immune cells modulate CRC response by infiltrating the CRC microenvironment [3,4]. Among these immune cells, type 2 innate lymphoid cells (ILC2s) are abundant in the gut to regulate the gut homeostasis [5,6]. However, the role and underlying mechanism by which ILC2 involves CRC development has not been elucidated.…”
Section: Introductionmentioning
confidence: 99%